Writing Gravity: International Female Graduate Students’ Academic Writing Experiences - Eldaba, Abir Aly; Isbell, Janet Kesterson (Journal of International Students, 2018)
In a critical study, researchers explored academic writing experiences of three international female graduate students at a southern U.S. university in order to understand their perspectives of themselves as writers across cultures, their experiences with academic writing, and their coping strategies for academic writing assignments. Findings revealed participants’ challenges and self-doubts about second-language writing abilities. Participants both challenged disconfirmation of their writing and at times were submissive as they negotiated a graduate degree program. The study demonstrates need for universities to recognize marginalized groups’ knowledge and ways of knowing and to create spaces to discuss new possibilities for academic writing experiences among international students.